Artificial Intelligence and the Future of Work in the Indonesian Public Sector - Ferry Silitonga; M Falikul Isbah (Universitas Pendidikan Ganesha, 2023)
This study explores the adoption of Artificial Intelligence (AI) in the public sector, particularly how AI adoption affects employment and the future of work. The questions are what the correlation between AI and the future of work is and how the Indonesian government has developed strategies to adopt AI in the public sector. We sought data from various sources and found Indonesia’s National Strategy on AI, published by the National Research and Innovation Agency (BRIN), to be the most relevant. We reviewed and discussed the paper by cross-referencing with the emerging studies on AI in the global context. We found a strong link between AI adoption and changing employment structure, which requires skills upgrades and human resource deployment restructure. Looking into the sectors more closely, we argue that AI adoption will dramatically change the nature of work and employment structure in healthcare and bureaucracy but will only moderately affect education, food security, mobility, and smart cities.